Pengaruh Return on Assets (ROA), Return on Equity (ROE), dan Earning per Share (EPS) terhadap harga saham: (Studi Empiris Pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020) - Debbie Christine; Winarti Winarti (Politeknik Ganesha Medan, 2022)
It is important for investors before making an investment to know how the performance of a company can be seen from the financial statements. Financial statements are information that can assist in making decisions, one of which is investment. Where profitability is one aspect that must be considered, profitability is the company's ability to utilize existing resources to achieve profits. This study was conducted to empirically test the effect of profitability on stock prices as measured by the ratio of Return on Assets (ROA), Return on Equity (ROE) and Earning Per Share (EPS). This research was conducted on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The population of this study were 26 companies. The sampling technique in this study used a non-probability sampling method, namely purposive sampling. The sample in this study were 20 companies. The type of data used is secondary data using financial reports obtained from the official website of the Indonesia Stock Exchange. This research was conducted using the classical assumption test method, multiple linear regression analysis, and hypothesis testing (t test and F test). The results of this study prove that partially and simultaneously profitability using the ratio of Return on Assets (ROA), Return on Equity (ROE) and Earning Per Share (EPS) affect stock prices.